Jesse R. answered • 09/21/18

Tutor

New to Wyzant
Experienced Math Tutor

We can represent this with a system of equations.

Let the amount of money Jim has be represented by x, and the amount of money Dave as be represented by y.

Dave and Jim, together, have $78. Thus, x+y=78.

Jim has $6 more than dave. In other words, x=y+6

Now we have our two equations. We want to solve for x, the amount of money Jim has. We can do this by rearranging the first equation to get y=78-x.

Let the amount of money Jim has be represented by x, and the amount of money Dave as be represented by y.

Dave and Jim, together, have $78. Thus, x+y=78.

Jim has $6 more than dave. In other words, x=y+6

Now we have our two equations. We want to solve for x, the amount of money Jim has. We can do this by rearranging the first equation to get y=78-x.

Now we can replace the y in the second equation with 78-x. This gives us x=(78-x)+6. We can now solve for x easily.

x=78-x+6

2x=78+6

2x=84

x=42